Distribuição de macrófitas aquáticas em relação a um gradiente ambiental na bacia do Rio Itanhaém, SP - Mori, Gisele Biem [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Environmental gradients have been widely used as an ecological framework to understand the dynamic and functioning of ecosystems. Watersheds show a different aspect because of the connectivity of rivers and streams in the drainage network, as proposed in the River Continuum Concept (RCC). The aquatic macrophytes, an important component of the aquatic flora, respond to environmental characteristics that influence their occurrence and distribution. In this study we verify the presence of an environmental gradient of abiotic characteristics and macrophytes distribution in a river’s stretch in the Itanhaém river basin, São Paulo, in order to understand if it can be explained by the RCC; and verify which abiotic characteristics are more important in the occurrence of species of aquatic macrophytes. The sampling was realized in downstream-upstream direction in 51 sampling points (500 meters of distance between them) of abiotic variables (limnological and of the channel) and occurrence of the species was determinate by the presence and absence of them in the points. The species of the study were: Egeria densa, Cabomba furcata, Potamogeton pusillus, P. polygonus, Utricularia foliosa, Pistia stratiotes e Salvinia molesta.The abiotic variables and the species occurrence were analysis in scatterplots in relation to the distance between the sampling points to verify the presence of the gradient along the stretch and were adjusted in linear models. The importance of abiotic variables for species occurrence was analyzed by Generalized Linear Models (GLM). To verify the importance of the group of variables in the community was realized a Partial Redundancy Analysis (pRDA). Our results showed that the stretch presents an environmental gradient of abiotic characteristics and species distribution as proposed by the RCC. Egeria densa and C. furcata were the more abundant species and were related to total phosphorus of the substrate, channel depth and...

Gradientes ambientais têm sido utilizados amplamente como ferramenta ecológica para se compreender a dinâmica e o funcionamento dos ecossistemas, sendo que em bacias hidrográficas apresentam um diferencial pela conectividade que os rios e riachos apresentam dentro do sistema de drenagem, como proposto pelo Conceito do Contínuo Fluvial (River Continuum concept - RCC). As macrófitas aquáticas, um componente importante da flora aquática, respondem às características ambientais que influenciam sua ocorrência e distribuição. Neste estudo buscou-se verificar a ocorrência de um gradiente de características abióticas e de distribuição de macrófitas aquáticas em um trecho de rio da bacia do rio Itanhaém, São Paulo, com a finalidade de compreender se o funcionamento deste trecho pode ser explicado pelo RCC; e verificar quais características abióticas são mais importantes na ocorrência de macrófitas aquáticas. A amostragem foi realizada no sentido foz-cabeceira em 51 pontos amostrais (com 500 metros de distância entre si) de variáveis abióticas (limnológicas e do canal), e a ocorrência das espécies foi determinada através da presença ou ausência delas nos pontos. As espécies de macrófitas aquáticas estudadas foram: Egeria densa, Cabomba furcata, Potamogeton pusillus, P. polygonus, Utricularia foliosa, Pistia stratiotes e Salvinia molesta. As variáveis abióticas e a ocorrência das espécies foram plotadas em gráficos scatterplots em relação à distância entre os pontos, para verificar a presença do gradiente ao longo do trecho e ajustados modelos lineares para cada variável. A importância das variáveis abióticas para a ocorrência das espécies foi analisada por meio de Modelos Lineares Generalizados (GLM). Para verificar a importância do conjunto de variáveis em todas as espécies (comunidade) foi realizada uma Análise de Redundância Parcial (pRDA). Nossos resultados mostraram que as variáveis...
Keywords: Aquatic ecology; Ecologia aquatica; Macrófitas aquáticas; Macrófitas aquáticas - Distribuição geográfica; Itanhaém, Rio, Bacia (SP)